Dengue virus Non-structural (NS) 1 gene as a molecular marker for early detection of in vitro dengue virus infection - Nur Azizah A Rahman,; Fadhilah Moh Djamil,; Vinod RMT Balasubramaniam,; Sharifah Syed Hassan,; Wei, Boon Yap (Penerbit Universiti Kebangsaan Malaysia, 2021)
Serology-based dengue assays at times produce inaccurate results especially in the early phase of disease onset. A more precise diagnostic approach detecting dengue infections in the early phase enables better management of the disease. This helps reduce dengue-associated morbidity and mortality. Besides, an early diagnosis of dengue is also very beneficial in a dengue outbreak and in endemic regions. In this light, this study aimed to determine the potential of the dengue virus (DENV) non-structural 1 (NS1) gene as an early detection biomarker. The cytopathic effects (CPE) were monitored and the cell death of DENV serotype-2 (DENV2)-infected Vero cells was evaluated for fourteen consecutive days. Only Lemos and in-house NS1-specific primer pairs showed positive amplifications in the preliminary primer validation. Thus, both of the primer pairs were then used to amplify the NS1 gene from the infected cells. The NS1 gene was detected as early as day-2 post-infection using the in-house primers. There was no amplicon produced using the Lemos primers. This is speculated to be attributable to the relatively lower complementarity of the primer sequences with that of the template and low amount of viral mRNA in the DENV2-infected cells. Conclusively, the DENV NS1 gene is a potential early detection marker, however, the NS1-specific primers should be pre-validated to ensure a reliable dengue diagnosis.